Utilizing Shear Factor Model and Adding Viscosity Term in Improving a Two-Dimensional Model of Fluid Flow in Non Uniform Porous Media - Yazid Bindar; IGBN Makertihartha; M. Dani Supardan; Luqman Buchori (Journal of Engineering and Technological Sciences, 2007)
In a packed bed catalytic reactor, the fluid flow phenomena are very complicated because the fluid and solid particle interactions dissipate the energy. The governing equations  were developed in the  forms of  specific  models. The shear factor  model was introduced in the momentum equation for covering the effect  of  flow  and  solid  interactions  in  porous  media.   A  two  dimensional numerical  solution  for  this  kind  of  flow  has  been  constructed  using  the  finite volume  method.  The  porous  media  porosity  was  treated  as  non-uniform distribution  in  the  radial  direction.  Experimentally,  the  axial  velocity  profiles produce  the  trend  of  having  global  maximum  and  minimum  peaks  at  distance very close to the wall. This trend is also accurately picked up by the numerical result. A more comprehensive shear factor formulation results a better velocity prediction than other correlations do. Our derivation on the presence of porous media leads to an additional viscosity term. The effect of this additional viscosity term was investigated numerically. It is found that the additional viscosity term improves  the  velocity  prediction  for  the  case  of  higher  ratio  between  tube  and particle diameters